Law Librarianship in the Twenty-First Century - Balleste, Roy; Luna-Lamas, Sonia; Smith-Butler, Lisa (Rowman & Littlefield Publishers, 2006)
The role of providing public access to the law is a critical one for librarians. It has been over ten years since the last law librarianship textbook was published. Since that time, much has changed in the profession, and with the emergence of new technologies such as artificial intelligence and quantum computing, law librarians must master legal materials and a thorough understanding of the latest technologies in order to best serve the public. Law Librarianship in the 21st Century, a text for library and information science courses on law librarianship, introduces students to the rapidly evolving world of law librarianship. With no prior knowledge of the law required, students using this book will find practical answers to such questions as: What is law librarianship? How do you become a law librarian? How does law librarianship interrelate with the legal world? Individual chapters provide a concise treatment of such specialized topics as the history of law librarianship, international law, and government documents. Standard topics are dealt with as they apply to the law library, including collection development, public services, technical processing, administration, technology, and consortia. The textbook also includes an explanation of the common acronyms and special terminology needed to work in a law library.